2005
DOI: 10.1038/nature04069
|View full text |Cite
|
Sign up to set email alerts
|

Secondary craters on Europa and implications for cratered surfaces

Abstract: For several decades, most planetary researchers have regarded the impact crater populations on solid-surfaced planets and smaller bodies as predominantly reflecting the direct ('primary') impacts of asteroids and comets. Estimates of the relative and absolute ages of geological units on these objects have been based on this assumption. Here we present an analysis of the comparatively sparse crater population on Jupiter's icy moon Europa and suggest that this assumption is incorrect for small craters. We find t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

8
136
1

Year Published

2016
2016
2017
2017

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 108 publications
(146 citation statements)
references
References 21 publications
8
136
1
Order By: Relevance
“…In contrast to primary craters, diameters of secondary craters are usually limited by the diameter of their parent craters. T he upper limit of diameters for secondary craters is typically around 5% of the parent crater, as assumed by (Bierhaus et al, 2001(Bierhaus et al, , 2005. T he secondary crater population predicted by these studies is proportional to the primary population observed in the small diameter range (McEwen and Bierhaus, 2006).…”
Section: Seco Ndary Cratersmentioning
confidence: 97%
See 4 more Smart Citations
“…In contrast to primary craters, diameters of secondary craters are usually limited by the diameter of their parent craters. T he upper limit of diameters for secondary craters is typically around 5% of the parent crater, as assumed by (Bierhaus et al, 2001(Bierhaus et al, , 2005. T he secondary crater population predicted by these studies is proportional to the primary population observed in the small diameter range (McEwen and Bierhaus, 2006).…”
Section: Seco Ndary Cratersmentioning
confidence: 97%
“…In contrast, secondary craters were formed by impacts of pieces of material ejected during much lar ger primary impacts (Bierhaus et al, 2005).…”
Section: Seco Ndary Cratersmentioning
confidence: 99%
See 3 more Smart Citations